Los cautivos del bosque - Marryat, Frederick, 1792-1848 (Colección Grandes clásicos., 2015)
Orphaned when their Royalist father is killed during the Civil War, the four Beverley children are taken into hiding in a cottage in the New Forest and disguised as the grandchildren of a poor forester.